2004
DOI: 10.1152/ajpregu.00265.2003
|View full text |Cite
|
Sign up to set email alerts
|

Mutual dependence of VIP/PACAP and CCK receptor signaling for a physiological role in duck exocrine pancreatic secretion

Abstract: Unlike in rodents, CCK has not been established as a physiological regulator in avian exocrine pancreatic secretion. In the isolated duck pancreatic acini, 1 nM CCK was required for stimulation of amylase secretion, maximal effect being achieved at 10 nM; picomolar CCK was without effect. Vasoactive intestinal peptide (VIP)/pituitary adenylate cyclase activating peptide (PACAP) receptor (VPAC) agonists PACAP-38 and PACAP-27 (10-12-10-7 M) alone had no effect, but made picomolar CCK effective. VPAC agonist VIP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
27
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 41 publications
4
27
0
Order By: Relevance
“…Redrawn from data published in Ref. 149. B: low, physiological concentrations of CCK alone do not stimulate amylase secretion in freshly isolated duck pancreatic acini; only when CCK concentration reaches supraphysiological levels will it have a stimulatory effect on amylase secretion, with a maximal stimulatory concentration of 10 nM (solid blue line).…”
Section: Cck Stimulation Of Exocrine Pancreatic Secretion: Direct Andmentioning
confidence: 98%
See 4 more Smart Citations
“…Redrawn from data published in Ref. 149. B: low, physiological concentrations of CCK alone do not stimulate amylase secretion in freshly isolated duck pancreatic acini; only when CCK concentration reaches supraphysiological levels will it have a stimulatory effect on amylase secretion, with a maximal stimulatory concentration of 10 nM (solid blue line).…”
Section: Cck Stimulation Of Exocrine Pancreatic Secretion: Direct Andmentioning
confidence: 98%
“…Further examination of the dose-response curve revealed that rodent CCK1Rs are exceptionally sensitive to CCK, with a threshold concentration at 1 pM (23,57,115,149). Picomolar CCK concentrations induced significant amylase secretion in all isolated rodent (rat, mouse, and guinea pig) pancreatic acini, and maximal stimulating CCK concentration was 100 pM (149).…”
Section: Cck Stimulation Of Exocrine Pancreatic Secretion: Direct Andmentioning
confidence: 99%
See 3 more Smart Citations